Two conceptions of economics - Crespo, Ricardo Fernando (2011)
As Ronald Coase points out, there are two kinds of conceptions of economics: first, the conception that emphasizes the study of specific kinds of human activities; and, second, the conception that makes economics the study of a specific approach to all human choices. The paper first shortly reviews the two conceptions. Then, it links them to specific conceptions about rationality. An analysis of the terms involved in the discussion shows which conception of economics corresponds most to its ordinary language meaning. The paper then analyzes and develops Coase's argument for the first and against the second conception, explores the limits of an integration of the two views and assigns them specific roles.